Calculation of time-temperature dependence of vulcanization in manufacture of rubber-reinforced tracks - A. M. Tolstov; L. N. Yurtsev; I. V. Veselov (Тонкие химические технологии)
In this work the problem of choosing time and temperature for the vulcanization of rubber mixtures is considered. In order to solve this task program MATLAB 7.0 was used. The program solves it as a type I differential equation of thermal conductivity by analytical method. The dependence of the change in temperature throughout the thickness of a plate from the heating and cooling of press forms-plates of a press is established. The temperature-time cycle cycle of the vulcanization for the manufacture of rubber-reinforced tracks was determined. During the research the vulcanization of real samples of rubber-reinforced tracks was performed. The results of physico-mechanical tests of rubbers of cured samples of rubber-reinforced tracks are in agreement with the characteristics for these rubbers established in the quality specification.